Mediation-Moderation Links Between Mothers' ACEs, Mothers' and Children's Psychopathology Symptoms, and Maternal Mentalization During COVID-19 - Dollberg, Daphna G.; Hanetz-Gamliel, Keren (Frontiers in Psychiatry, 2022)
Research has suggested adverse childhood experiences (ACEs) as a transdiagnostic risk factor for a variety of affective disorders. They are also linked with a parent's tendency toward affect dysregulation and hyperarousal, which may interfere with parenting and children’s wellbeing. On the other hand, maternal mentalization can serve as a moderating factor that can help parents regulate their arousal, shielding children during adverse circumstances. We studied the mediated links between ACEs and mothers’ and children’s psychopathology symptoms during COVID-19 to determine whether maternal mentalization and the child’s age moderate these links. Using results from 152 Israeli mothers of children aged 3-12 years recruited during the month-long lockdown in Israel, we documented that the mothers’ ACEs were linked with increased risk of depressive and anxiety symptoms and with children’s internalizing and externalizing behaviors. Moreover, as hypothesized, the mothers’ symptoms of depression and anxiety mediated the links between their ACEs and their children’s internalizing behaviors. In addition, the mothers’ mentalization skills and, in the case of their depressive symptoms, their child's age moderated these indirect links. For mothers of young children (3-6 years old) with higher mentalization levels, the link between the mothers’ ACEs and the children’s behavior problems was weaker compared to mothers with low mentalization levels. For mothers of older children (6-12 years old), and only in the case of maternal depressive symptoms, higher levels of maternal mentalization were linked with more internalizing behaviors. We discuss the potential clinical implications of the findings.